Elie Wiesel, messenger from the Holocaust - Greene, Carol (Picture-story biographies., 1987)
A brief biography of the winner of the 1986 Nobel Peace Prize, who having survived the Holocaust, dedicated his life to speaking and writing about these terrible events so that they would not be forgotten.